Making Banks Safer : Can Volcker and Vickers Do it? - Chow, Julian (IMF Working Papers; Working Paper ;, 2011)
This paper assesses proposals to redefine the scope of activities of systemically important financial institutions. Alongside reform of prudential regulation and oversight, these have been offered as solutions to the too-important-to-fail problem. It is argued that while the more radical of these proposals such as narrow utility banking do not adequately address key policy objectives, two concrete policy measures - the Volcker Rule in the United States and retail ring-fencing in the United Kingdom - are more promising while still entailing significant implementation challenges. A risk factor common to all the measures is the potential for activities identified as too risky for retail banks to migrate to the unregulated parts of the financial system. Since this could lead to accumulation of systemic risk if left unchecked, it appears unlikely that any structural engineering will lessen the policing burden on prudential authorities and on the banks.